Pengaruh Electronic Word of Mouth dan Web Quality Terhadap Kepercayaan Konsumen Pada Toko Online Lazada di Kota Pariaman - Vebriana, Vellia; Salfina, Lili; Zaki, Fakhri (Jurnal Pustaka Manajemen (Pusat Akses Kajian Manajemen), 2025)
This research aims to determine the influence of electronic word of mouth and web quality on consumer trust in the Lazada online store in Pariaman City. The population in the study was the people of Pariaman City with a sample of 81 respondents. This type of research is quantitative. The research data source uses primary data obtained from distributing questionnaires which were tested for validity and reliability. The data analysis technique in this research uses multiple linear regression, classical assumption testing, hypothesis testing and coefficient of determination. Data processing in this study used the SPSS version 29 program. The research results obtained a multiple liner regression value Y = 0.850 + 0.267 X1 + 0.589 web quality has a positive and significant influence on Lazada consumer trust in Pariaman City, and simultaneously electronic word of mouth and web quality have a positive and significant influence on Lazada consumer trust in Pariaman City. From the results of the coefficient of determination, the Adjusted Rsquare value is 0.743, meaning that the independent variable is able to influence the dependent variable by 74.3% while the remaining 25.7% is influenced by other variables not examined in this research.